ANALISIS FAKTOR – FAKTOR YANG MEMENGARUHI MINAT BERKUNJUNG KE EVENT EDU EXPO: Studi Kasus Event SKAFOURTA EXPO Yogyakarta - Rina Kuswardani; Nining Yunianti; Isdarmanto (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
This study aims to describe and understand the factors that influence the interest in visiting the Edu EXPO event at SKAFOURTA EXPO YOGYAKARTA. The research design used is quantitative design. The data used is primary data in the form of questionnaires distributed to visitors of SKAFOURTA EXPO event. The sample used was 292 visitors as informants. The results showed that the F-test results showed that the calculated F value was 81.552 with a p-value (significance) of 0.000, the significance value of the F-test is smaller than 0.05 (0.000 <0.05), it can be concluded that the independent variables including entertainment, excitement, enterprise, and price perception simultaneously have a significant effect on visiting interest. The T-test results show that, a) the significance value of entertainment is 0.153, and significant because its p-value = 0.000 < 0.05; b) the significance value of excitement is 0.103, and significant because its p-value = 0.014 < 0.05; c) the significance value of enterprise is 0.461, and significant because its p-value = 0.000 < 0.05; d) the significance value of price perception is 0.258, and significant because its p-value = 0.000 < 0.05. In conclusion, partially and simultaneously show that entertainment, excitement, enterprise and price perception factors affect the interest in visiting the EDU EXPO EVENT at SKAFOURTA EXPO YOGYAKARTA.